السياسة الخارجية الليبية تجاه دول الجوار: تونس أنموذجا - بعيو، توفيق مصطفى (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Libya's foreign policy has gone through several phases, making it different from one stage to the next and making it surrounded by ambiguity. As a result of this ambiguity, a number of questions arise in our minds, on what basis have these changes taken place? What is its relationship with neighboring countries? Especially the Republic of Tunisia? And how was Libya's foreign policy towards it throughout the period identified for the study? And the tools used by the Libyan state in implementing its foreign policy in general and Tunisia in particular. The importance of this research is to know the extent and strength of Libya's foreign policy, to highlight Libya's foreign policy under Gaddafi and the role of political elites in the era of Gaddafi and February 17. And this research aims to highlight the features of Libya's foreign policy and mentioned how the state of Libya and its political system was established, and a set of approaches for this research was used for historical research, analytical descriptive methodology and comparative methodology. The research showed several results: The role of political elites in the era of Gaddafi was very limited, unlike their role in the period of the February 17 era. The Libyan state during the Gaddafi era was tigtly controlled by him and consequently collapsed with his downfall. Libyan-Tunisian relations during the era of Gaddafi were excellent, and specifically during the period of former President Zine El Abidine Ben Ali. The researcher recommends: Paying more attention to the relations with neighboring Tunisia.Securing the borders between the two countries, preventing the infiltration of smugglers and outlaws of the two sides, and protecting the economy of the two countries. The researcher recommends the Involement of all categories of Libyan society without the exclusion of any particular categoy, regardless of its affiliation, ending the law of political isolation, and accelerating the enacting of the Constitution.